2021
DOI: 10.20944/preprints202105.0160.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

WhatsApp as an ICT Tool in Higher Education- a Survey During COVID Pandemic in the State of Goa

Abstract: The Coronavirus outbreak that began in December, 2019 became a worldwide pandemic by March, 2020. The education industry had to adapt to this new change in a speedy and most feasible way by shifting to virtual classes over the internet and other available resources. WhatsApp has turned out to be a boon in academic’s section where in all the teachers have their own subject-wise groups on the said application. This not only helps them to share the necessary information resources but also to have discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…- ---------------------------------------------------------------------------------------------------------------- The result of this research also supported by Sawant & Chari (2021) technology contributes to technology addiction so that stress arising out of it with overload information also, interpersonal communication among the students will be the most concerning issue due to lack of face to face communication and this could affect their mental state also. Research done by Gon & Rawekar, (2017) agree with the current study that the disadvantages of whatsapp as a learning tool are message flooding, time consuming and eye strain.…”
Section: Theme 1: How Students Use Whatsapp As a Learning Medium During The Covid-19 Pandemic?supporting
confidence: 77%
See 1 more Smart Citation
“…- ---------------------------------------------------------------------------------------------------------------- The result of this research also supported by Sawant & Chari (2021) technology contributes to technology addiction so that stress arising out of it with overload information also, interpersonal communication among the students will be the most concerning issue due to lack of face to face communication and this could affect their mental state also. Research done by Gon & Rawekar, (2017) agree with the current study that the disadvantages of whatsapp as a learning tool are message flooding, time consuming and eye strain.…”
Section: Theme 1: How Students Use Whatsapp As a Learning Medium During The Covid-19 Pandemic?supporting
confidence: 77%
“…Based on a study conducted by Sawant & Chari, (2021) WhatsApp is an effective tool for ICT in Higher Education but it must be used wisely and cautiously by both the teachers and the students.…”
Section: Theme 1: How Students Use Whatsapp As a Learning Medium During The Covid-19 Pandemic?mentioning
confidence: 99%
“…In addition, these applications are easy to operate and are commonly used. The finding of the study done by (Sawant & Chari, 2021;Pustikayasa, 2019;Pratama & Kartikawati, 2017;(Jain, Luaran, & Rahman, 2016;Tamim, Colburn, Saadi, & Qunneis, 2016) also found that technology applications gave the benefit on online learning and it helped the students and teacher in sharing the source information. Next, the same finding showed that the zoom meeting has made it easier for the process of interacting during the covid-19 pandemic (Erna, Asriani, Genisa, Muslaini, & Suhartini, 2022).…”
Section: Documentmentioning
confidence: 94%
“…So, learning discussion activities continue using class group WA. Thus, everyone has a different perception of written information in WA, and it is a tool of communication nowadays in the learning process (Sawant & Chari, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The application of WhatsApp media can improve student learning outcomes, especially during the Covid-19 pandemic (Kartini, 2021;Djamdjuri & Kamilah, 2020). On the other hand, this app allows easy access for students to all the resources shared by teachers, and they can share assignments without much hassle with their subject teachers (Sawant & Chari, 2021). In addition, the use of the WhatsApp application is also quite familiar among students.…”
Section: Introductionmentioning
confidence: 99%